Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3389/fpubh.2022.1038138
|View full text |Cite
|
Sign up to set email alerts
|

Improving Initial Medication Adherence to cardiovascular disease and diabetes treatments in primary care: Pilot trial of a complex intervention

Abstract: IntroductionThe Initial Medication Adherence (IMA) intervention is a multidisciplinary and shared decision-making intervention to improve initial medication adherence addressed to patients in need of new treatments for cardiovascular diseases and diabetes in primary care (PC). This pilot study aims to evaluate the feasibility and acceptability of the IMA intervention and the feasibility of a cluster-RCT to assess the effectiveness and cost-effectiveness of the intervention.MethodsA 3-month pilot trial with an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…This study focuses on a topic that is not widely discussed in the literature yet. However, if the impact of the COVID-19 epidemic on interruptions of antihypertensive treatment has been little assessed, several studies have shown a worrying decrease in the use of chronic drugs over the pandemic, in fields as various as mental disorders ( Mansfield et al, 2021 ; Sanchez et al, 2022 ) or diabetes for instance ( Corral-Partearroyo et al, 2022 ; Mathieu et al, 2022 ). Considering more specifically cardiovascular drugs, our results appear consistent with those of a study assessing the impact of the epidemic on adherence to statins ( Malo et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…This study focuses on a topic that is not widely discussed in the literature yet. However, if the impact of the COVID-19 epidemic on interruptions of antihypertensive treatment has been little assessed, several studies have shown a worrying decrease in the use of chronic drugs over the pandemic, in fields as various as mental disorders ( Mansfield et al, 2021 ; Sanchez et al, 2022 ) or diabetes for instance ( Corral-Partearroyo et al, 2022 ; Mathieu et al, 2022 ). Considering more specifically cardiovascular drugs, our results appear consistent with those of a study assessing the impact of the epidemic on adherence to statins ( Malo et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%